IMP2ART systematic review of education for healthcare professionals implementing supported self-management for asthma. (December 2018) - McCleary, Nicola; Andrews, Amanda; Buelo, Audrey; Captieux, Mireille; Morrow, Susan; Wiener-Ogilvie, Sharon; Fletcher, Monica; Steed, Liz; Taylor, Stephanie; Pinnock, Hilary
Abstract Despite a robust evidence base for its effectiveness, implementation of supported self-management for asthma is suboptimal. Professional education is an implementation strategy with proven effectiveness, though the specific features linked with effectiveness are often unclear. We performed a systematic review of randomised controlled trials and controlled clinical trials (published from 1990 and updated to May 2017 using forward citation searching) to determine the effectiveness of professional education on asthma self-management support and identify features of effective initiatives. Primary outcomes reflected professional behaviour change (provision of asthma action plans) and patient outcomes (asthma control; unscheduled care). Data were coded using the Effective Practice and Organisation of Care Taxonomy, the Theoretical Domains Framework (TDF), and Bloom's Taxonomy and synthesised narratively. Of 15, 637 articles identified, 18 (reporting 15 studies including 21 educational initiatives) met inclusion criteria. Risk of bias was high for five studies, and unclear for 10. Three of 6 initiatives improved action plan provision; 1/2 improved asthma control; and 2/7 reduced unscheduled care. Compared to ineffective initiatives, effective initiatives were more often coded as being guideline-based; involving local opinion leaders; including inter-professional education; and addressing the TDF domains 'social influences'; 'environmental context and resources'; 'behavioural regulation'; 'beliefs about consequences'; and 'social/professional role and identity'. Findings should be interpreted cautiously as many strategies were specified infrequently. However, identified features warrant further investigation as part of implementation strategies aiming to improve the provision of supported self-management for asthma.